EASY WAYS TO REMEMBER IDIOMS IN THE ENGLISH LANGUAGE - Mamadaliyeva Gulbahor Arabjanovna (Лучшие интеллектуальные исследования, 2024)
Abstract: Idioms are an essential part of language that add color and depth to our communication. However, remembering them can be a challenge for many language learners. This article explores some easy and effective ways to remember idioms in the English language.